Eosinophilic esophagitis in the “atopic march”: dupilumab as an “umbrella” strategy for multiple coexisting atopic diseases - Lutzu, Nicola; Favale, Agnese; Demurtas, Mauro; Del Giacco, Stefano; Onali, Sara; Fantini, Massimo Claudio (Frontiers in Medicine, 2025)
Dupilumab is a monoclonal antibody targeting interleukin-4 and interleukin-13, approved for the treatment of multiple T2 diseases and more recently for Eosinophilic Esophagitis (EoE). EoE is a chronic T2 inflammatory disease, believed to be a member of the “atopic march”, due to multiple similarities with other atopic diseases, ranging from epidemiology to genetics and pathophysiology. Although often co-existing in the same patient, these diseases are still treated as separated entities by different specialists, resulting in polypharmacy and chronic use of steroids. Thus, a shared-decision approach by a multidisciplinary team composed of different specialists might improve clinical management and outcomes. Yet, prospective data on the effectiveness of dupilumab as a single agent for multiple T2 inflammatory diseases are lacking, since only few case reports and small studies have been published so far reporting outcomes in patients affected by multiple T2 diseases. The purpose of this review is to illustrate the rationale and clinical evidence supporting the possibility of using dupilumab as a single therapeutic agent in those patients affected by multiple T2 diseases in addition to EoE.